The manager's bookshelf a mosaic of contemporary views - Pierce, Jon L.; Newstrom, John W. (Upper Saddle River, New Jersey Pearson education, Inc., 2014)
This is a collection of objective summaries from a broad sampling of bestselling business books. Presenting readers with a collage of information to improve their knowledge of management practices, this text introduces the philosophies, views, and experiences of several authors whose works have captivated the attention of today's management community.
International edition.
ncludes bibliographical references and index.
Keywords: Management literature -- United States